Characterization of indigenous chicken phenotypes in Liban Jawi District, Ethiopia: A qualitative and quantitative analysis. - Desalegn Begna; Teferi Bacha; Shamble Boki; Kasahun Bekana (PLoS ONE)
Indigenous chickens play a crucial role in the livelihoods of smallholder farmers in rural Ethiopia. This study aimed to phenotypically characterize indigenous chickens in the Liban Jawi district, focusing on measurements of phenotypic characteristics. The multi-stage sampling method selected 192 households with at least two mature indigenous chickens from 2,166 households, resulting in the sampling of 224 chickens (138 females and 86 males) for phenotypic characterization. Qualitative trait analysis revealed that male chickens exhibited a plain head shape (54.7%), single combs (39.5%), red feather plumage (26.7%), yellow shanks (54.7%), red earlobes (51.6%), and white skin (68.6%). Female chickens showed single combs (75.4%), red earlobes (51.4%), yellow shanks (50.1%), and brown mottled feathers (23.9%), with red (23.1%) and black (9.4%) feathers observed. Quantitatively, cocks had an average body weight of 1.46±0.02 kg, while hens weighed 1.21±0.01 kg. Cocks exhibited larger body dimensions, with significant measurements in body length (38.05±0.26 cm) and wingspan (38.56±0.13 cm). For hens, the average body length was 31.55±0.33 cm. Shank length emerged as a moderate predictor of body weight for both sexes (r = 0.45 for hens and r = 0.44 for cocks), indicating it should be combined with other factors for accurate assessments. Cluster and multivariate analysis revealed distinct phenotypic groupings among the indigenous chickens, highlighting significant variations in both qualitative and quantitative traits. This suggests the potential for improvement through selective breeding at the community level, influenced by unique environmental conditions and practices. These findings provide valuable insights into the phenotypic characterization of indigenous chickens, serving as a foundation for future breeding programs and conservation efforts aimed at enhancing productivity and preserving genetic diversity. Further molecular-level characterization is recommended to validate the current phenotypic results.